Responsivitas Dinas Kesehatan Kabupaten Sragen dalam Upaya Mengurangi Angka Stunting pada Balita - Erna Widyawati; Sudaryanti Sudaryanti (Jurnal Mahasiswa Wacana Publik, 2022)
The problem of the stunting rate in Sragen Regency is still considered high, from data from the Ministry of Health BPS, the March 2019 Susenas Integration and the 2019 SGBI when compared to other districts in the former Surakarta residency, it can be said that Sragen Regency has the highest stunting rate, which is around 32.40%. . From these problems, of course, a comprehensive and integrated handling is needed by government elements through related agencies and has and is authorized in the public health sector, including the Sragen District Health Office. This study aims to determine and describe how the Responsiveness of the Sragen District Health Office in an effort to reduce stunting rates in toddlers. This study uses a type of research with qualitative descriptive methods, and the data used consists of primary and secondary data, obtained from interviews, observations and documentation. The sampling technique is purposive sampling. The validity of the data using triangulation of sources and methods/techniques. Furthermore, the data analysis technique was carried out using the Miles and Huberman interactive analysis model. The results showed that the responsiveness of the Sragen District Health Office in Efforts to Reduce Stunting Rates in Toddlers was responsive enough to know the needs of the community, had priority activities that had been prepared and was able to develop service programs such as innovating and collaborating with cross-sectors.